2013
DOI: 10.1186/1475-2840-12-108
|View full text |Cite
|
Sign up to set email alerts
|

Dual renin-angiotensin system inhibition for prevention of renal and cardiovascular events: do the latest trials challenge existing evidence?

Abstract: Circulatory and tissue renin-angiotensin systems (RAS) play a central role in cardiovascular (CV) and renal pathophysiology, making RAS inhibition a logical therapeutic approach in the prevention of CV and renal disease in patients with hypertension. The cardio- and renoprotective effects observed with angiotensin-converting enzyme (ACE) inhibitors or angiotensin II receptor blockers (ARBs) monotherapy, together with the availability of a direct renin inhibitor (DRI), led to the investigation of the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 104 publications
(120 reference statements)
2
3
0
Order By: Relevance
“…40 Increased osteopontin and TGF-β expression seems to be caused both by angiotensin II-dependent and independent mechanisms. Conversely, therapy with angiotensin-1 receptor antagonists and/ or inhibition of the renin angiotensin system with the use of angiotensinconverting enzyme inhibitors; including Lisinopril in this study ameliorates these structural and functional changes, 41 a finding that was confirmed by the results of treatment with Lisinopril in the present study.…”
Section: R E T R a C T E Dsupporting
confidence: 75%
“…40 Increased osteopontin and TGF-β expression seems to be caused both by angiotensin II-dependent and independent mechanisms. Conversely, therapy with angiotensin-1 receptor antagonists and/ or inhibition of the renin angiotensin system with the use of angiotensinconverting enzyme inhibitors; including Lisinopril in this study ameliorates these structural and functional changes, 41 a finding that was confirmed by the results of treatment with Lisinopril in the present study.…”
Section: R E T R a C T E Dsupporting
confidence: 75%
“…Thus, a recent meta-analysis of clinical trials recommended monotherapy over combined therapy. [30] According to the present study results, the patients on combined ACEi and ARB had significantly lower levels of the fasting blood sugar, which may indicate better control of their diabetes. However, the levels of glycosylated hemoglobin did not show statistically significant differences among the treatment groups and the control group.…”
Section: Discussionsupporting
confidence: 53%
“…ACE forms ANG II from ANG I, whereas ACE2 cleaves ANG II to form ANG(1-7) (33), counterbalancing the ANG II-promoting effects of ACE by preventing ANG II accumulation in tissues (12,70). The suppression of the ACE/ANG II axis of the RAS minimizes cardiovascular and renal complications (42).…”
Section: The Important Role Of Adam17 In Renin-angiotensin System Regmentioning
confidence: 99%